SISTEM INFORMASI LAPORAN PEMERIKSAAN KESEHATAN LANSIA DI RW.05 KELURAHAN PASEBAN BERBASIS WEB - Melati Kusuma Budiani; Addin Nullah Arifin; Oda Roswita Aprilia; Nilam Herti Apriyani; M. Arjun Jamaludin; Nita Merlina; Nurajijah Nurajijah (Evolusi : Jurnal Sains dan Manajemen, 2021)
The reporting of the posyandu for the elderly at RW 05, Paseban sub-district is still using the manual method. During the preparation of the report, there were many deficiencies in the completeness of reporting, one of which was writing the names of elderly patients incomplete, there was an inappropriate age of elderly patients, and data on the results of examinations of elderly patients were collected manually, so there is a concern that the data is lost or damaged. The purpose of this study is to create a system to avoid errors in reporting that can be overcome by using web-based reporting of elderly health checks. The method used in system development is the waterfall method. The stages took in making the program are analysis, design, coding, testing, and evaluation. The use of a web-based information system for elderly posyandu reporting can make it easier for cadres to input, search, process, and produce data on visits to elderly patients for the period of months and years. The system can manage elderly patient data, display the results of the recapitulation of reporting the results of the activities of elderly patients monthly and annually, and the system can print reports.